Dematerialization and capital maintenance: Two sides of the sustainability coin - Peter Bartelmus (Wuppertal Institut für Klima, Umwelt, Energie, 2002)
The reductionist trend of equalizing sustainable development with CO2control needs to be reversed - notwithstanding the significance of climate change. Conventional, 'compartmentalized' data systems impede an integrated vision andtreatment of the paradigm. New accounts and balances focus on the interactionbetween environment and economy. 'Greened' national accounts measure economic sustainability in terms of (produced and natural) capital maintenance; balances of material flows assess ecological sustainability as the dematerializationof production and consumption. Both concepts aim to preserve environmentalassets. They differ however with regard to the scope, strength and evaluation ofsustainability. First results for Germany indicate weak sustainability of theeconomy, owing to an increasing capital base. Strong sustainability is not in sight,though, since material throughput has not been reduced sufficiently. An 'Alliancefor Sustainable Development' is proposed to implement and sustain the paradigm.
urn:nbn:de:bsz:wup4-opus-13592
Keywords: 330; Dematerialization; capital maintenance; sustainability; environmental accounting; eco-tax; alliance for sustainable development; Nachhaltige Entwicklung; Stoffstrom-Management; Umweltschutz; Rohstoffpolitik; Umweltpolitik; Deutschland